Current state of atmospheric air pollution in Ukraine based on Sentinel-5P satellite data - Савенець, Михайло Валерійович; Дворецька, Ірина Віталіївна; Надточій, Людмила Михайлівна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Introduction. Industrial development and increasing traffic emissions cause air quality problems. The most accurate for air pollution analysis are ground-based data; however, it is very limited in space. Modelling could solve this problem, but huge amount of input information and limits of computational power make it difficult to analyze big territories with high resolution. Sentinel-5P satellite with TROPOMI instrument nowadays gives opportunities to monitor the air pollution with good spatial resolution. The purpose of the study is to analyse nitrogen dioxide, sulfur dioxide, carbon monoxide and formaldehyde spatial and temporal distribution over Ukraine and Black Sea and Azov Sea.Methods and raw data. There were selected Sentinel-5P data of NO2, SO2, CO and HCHO for the period from first data release in 2018 to June, 2019. Data processing implemented in Google Earth Engine using JavaScript programming in The Earth Engine Code Editor.Results and discussion. Joint analysis of NO2 tropospheric, stratospheric and total columns showed the prevailing of tropospheric NO2 content and therefore crucial role of anthropogenic emission sources. While background NO2 total column varies from 4·10-5 mol/m2 to 7·10-5 mol/m2, in the most polluted cities content exceeds 1·10-4 mol/m2. The highest values are observed in Kyiv and industrial cities in Donbas region. Some of them are situated in the area of Joint Forces Operation outside the demarcation line. Sentinel-5P data catch the large emissions from the local industries; however, no official confirmations about production volume are available. NO2 dispersion increase during winter with the values range from 1·10-5 mol/m2 to 3·10-5 mol/m2 over clean territories and 8·10-5 mol/m2 to 1·10-3 mol/m2 in industrial cities. Seasonal maximal observed during warm period in unpolluted regions and during winter in the cities. Cold seasonal NO2 content outbreaks in the mountains are the result of its transportation from industrial cities.Spatial distribution of CO total column over Ukraine is rather homogeneous because of CO lifetime in the atmosphere up to several months. It could be transported on the long distances, which makes identification of polluted regions difficult. However, several cities with maximal average values of more than 0.037mol/m2 prove the existence of extreme anthropogenic emissions. Overall background CO contents vary within 0.033–0.035 mol/m2. Coastal regions of the Black Sea and Azov Sea are more polluted by CO compared to the mainland, which could be the consequences of ships emissions. Temporal analysis of CO total column found 4 powerful emissions: three of them are anthropogenic in industrial cities and one is natural, connected with forest fires in Belarus and northern part of Rivne region in April, 2019.There is one location with huge SO2 emission in Ukraine, observed in Novyi Svit (Donetsk region) outside the demarcation line of Joint Forces Operation, which corresponds to Starobeshivska thermal power station. In general, higher SO2 contents are observed over Donetsk, Zaporizhia and Dnipro regions; also over the Black Sea and Azov Sea. For HCHO spatial distribution minimal values are typical for the Carpathians. It is well seen that SO2 content are higher in the Southern part of Ukraine than in the Western part.The research finds regularities in spatial distribution of pollutants over the sea area. During cold season higher concentrations could be observed over the main merchant vessels tracks in the Black Sea. In summer months, which coincide with the main tourist season, most polluted are shoreline area because of emissions from cabotage and fishing vessels.The study updates information about most polluted cities in Ukraine, especially in the regions with absence of ground-based measurements. Some of them are mentioned for the first time among other research. Air quality analysis in many industrial cities significantly changed over the last two years. It shows difficulties of long-term pollution forecast and scenarios based on historical data and observed trends. It is recommended to use ensemble modelling for this purpose with scenarios of emission reduction, increasing and temporal stability. Sentinel-5P data confirm the conclusions of previous research about dependence of NO2 annual cycle and seasonality phases shift from the level of anthropogenic load.Prospects for further research. Sentinel-5P spatial resolution expands the horizons for air pollution research. The most relevant are monitoring of short-term anthropogenic and natural emissions, pollutants’ seasonality changes in different macroclimatic conditions, research of ships emissions in Black Sea and Azov Sea, combination of satellite air pollution data with methods of “artificial intelligence” for individual emissions detection.